Efektivitas Penggunaan Media Bahan Sisa Kantong Plastik dalam Mengembangkan Kreativitas Anak Usia Dini di Taman Kanak-Kanak Pembina 01 Linggo Sari Baganti - Julia Nengsih, Selvi; Yulsyofriend, Yulsyofriend (Jurnal Family Education, 2022)
This problem is motivated by the use of learning media in developing children’s creativity is not appropriate so that learning is less interesting and boring for children in TK Pembina 01 Linggo Sari Baganti. The purpose of this study was developed to determine the development of children’s creativity through the media of plastic bag waste material in TK Pembina 01 Linggo Sari Baganti. This plastic bag waste material media produces various kinds of works that are adjusted by the theme in the kindergarten. The type of research used is quantitative with experimental methods in the form of quasi-experimental (quasi-experimental). The population of this research is TK Pembina 01 Linggo Sari Baganti, with the sampling technique that is purposive sampling, namely group B1 for the experimental class and group B2 for the control class, each with 10 children. The data collection technique uses a statement sheet, then the data is processed by a test (t-test). Based on data analysis, the experimental group average was 35.1 and the control group was 32.4. In the hypothesis test, it is known that the value of Sig. (2-tailed) is 0.033 < 0.05, this means that the hypothesis Ha is accepted and Ho is rejected. So it can be concluded that Plastic Bag Remaining Material Media is Effective in developing children’s creativity in TK 01 Linggo Sari Baganti TK for the academic year 2021/2022